Histological and morphofunctional parameters of the hypothalamic-pituitary-adrenal system are sensitive to daidzein treatment in the adult rat - Trifunović, Svetlana; Manojlović-Stojanoski, Milica; Nestorović, Nataša; Ristić, Nataša; Šošić-Jurjević, Branka; Pendovski, Lazo; Milošević, Verica (Elsevier BV, 2018)
The isoflavone, daidzein is a biologically active, plant-derived compound that interacts with estrogen receptors. Data from previous studies have suggested that daidzein exerts beneficial effects in many diseases; however, as an endocrine disrupter, it may also alter the functioning of the endocrine system. Data regarding the effect of daidzein on the morphofunctional and histological parameters of the hypothalamic-pituitary-adrenal (HPA) system is still lacking. Therefore, using the newCAST stereological software, we investigated the effects of chronic (21 days) daidzein treatment on corticotropin-releasing hormone (CRH) neurons within the hypothalamus and corticotropes (ACTH cells) in the pituitary, while image analysis was employed to-examine the intensity of fluorescence of CRH in the median eminence (ME) and adrenocorticotropin hormone in the pituitary in adult orchidectomized (Ovx) rats. Circulating ACTH and corticosterone levels were also analyzed. This study showed that daidzein treatment decreased the volume density of CRH neurons within the paraventricular nucleus as well as CRH immunofluorescence in the ME. The total number of ACTH cells was decreased, while ACTH cell volume and the intensity of ACTH fluorescence were increased following daidzein treatment. Both ACTH and corticosterone blood levels were increased after daidzein administration. The results of performed experiments clearly demonstrate that volume density of CRH neurons; total number and volume of ACTH cells, as well as stress hormones levels are vulnerable to the effects of daidzein.